Neurologic Complications of Intrauterine Herpes Simplex Virus Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Three case reports of intrauterine herpes simplex virus infection (HSV) and 61 cases published between 1963 and 2009 are reviewed by researchers at Baylor College of Medicine, Houston, TX.